Increasing soluble dietary fiber content and antioxidant activity of wheat bran through twin-screw extrusion pretreatment. Issue 9 (1st October 2020) - Wang, Zichao; Yan, Liming; Ning, Tao; Wang, Xueqing; Li, Ruifang; Zhang, Huiru
Abstract: As a by-product during flour production, wheat bran is mainly used as raw material for fodder or fermentation. In the present work, wheat bran was extruded with different moisture conditions and the consequently chemical component, absorption capacity, and antioxidant activity of treated wheat bran were analyzed. Results showed that extrusion decreased the particle size and crystallinity of wheat bran, but increased the soluble dietary fiber content of which from 3.08% to 11.78%. Meanwhile, water holding capacity, oil holding capacity for peanut oil and lard, and swelling capacity of WB-W-G-Na reached 5.67 g/g, 3.34 g/g, 3.58 g/g and 4.3 mL/g, respectively. Moreover, DPPH radical scavenging activity of WB-W-G-Na increased from 6.8% to 18.4% and hydroxyl radical scavenging activity increased from 5.3% to 15.9%. Overall, this work provides an excellent pretreatment method for increasing the functional activities of wheat bran in the food industry.